(untitled) (Biological Sciences - PJSIR, 2000)
The amount of individual metabolites of chloroquine present in the urine of Wistar Albino rats was determined. The desethylchloroquine and the 4 -amino -7 -chloroquinoline were identified in this study similar to those’obtained in man by previous investigations. The results of the investigation suggest that rat metabolises chloroquine in a similar way as’man.